Development of Smart Lead-Acid Battery Charger for Electric Vehicle Application - Ibrahim Nour, Mutasim (1999)
The battery charger is a critical part in an electric vehicle (EV) because it charges the battery, which is the weakest part of it. An unduly long charging time limits the use of the EV. Currently, it takes a long time to charge a battery of limited capacity, making EVs rather impractical to use. The objective of this thesis is to design, simulate, construct and test a smart charger for fast charging a battery. The charger consists of two units - the power processing unit and the battery management unit. The power processor is based on a step-down DC-to-DC converter topology. The battery management unit uses first a current control (constant current mode) and then voltage control (constant voltage mode) to charge the battery. The smart control mechanism is based on current and voltage sensing combined with sequenced average current and voltage control to charge the battery as fast as possible and to maximise its charge. The charger was tested successfully on single-phase and three-phase voltage supplies at different output voltages and currents. The charger developed was able to charge a 30 Ah lead-acid battery in two hours as opposed to six hours using a conventional charger. The research showed that it was possible to develop a battery charger which can charge a battery to its limits quickly without gassing and overheating. It is likely that the battery life will be extended without the detrimental effects experienced.